Coordinated Control of Parallel Power Conditioners Synthesizing Resistive Loads in Single-Phase AC Microgrids - Santos Alonso, Augusto Matheus dos [UNESP]; Brandao, Danilo Iglesias; Marafao, Fernando Pinhabel [UNESP]; Tedeschi, Elisabetta; IEEE (Ieee, 2019)
Without proper coordination, power conditioners within microgrids are prone to suffer from resonance phenomena due to the complex and dynamic interactions among the main grid, nonlinear loads and distributed converters. In addition to the detriment of grid-connected devices and loads, harmonic voltage resonances may also lead to microgrid instability. As a consequence, the steering of distributed power conditioners to diminish voltage distortions and suppress undesired currents has been playing a key role on enhancing the operational stiffness of microgrids. In general, such conditioners are driven by the synthesis of sinusoidal currents independently on the status of voltage waveforms, which may not adequately damp harmonic resonances and still jeopardize system stability. Thus, this work proposes the coordination of multiple parallel power conditioners, which are driven as controlled current sources, through a current-based approach that synthesizes resistive loads, enhancing the system capability to damp voltage resonances, as well as improving power quality within microgrids. Simulation results comprising a single-phase microgrid with resonant and nonlinear loads, as well as two distributed power conditioners, are presented to demonstrate the effectiveness of the approach.
Keywords: Harmonics; Load sharing control; Microgrid; Parallel operation; Power conditioning